Just in time [compact disc] : original Broadway cast recording - Chapin, Theodore S.; Groff, Jonathan; Groff, Jonathan; Leight, Warren; Oliver, Isaac; Lawrence, Gracie; Henningsen, Erika; Barbara, Joe (Actor); Roberts, Lance (Actor); Resnick, Andrew; Resnick, Andrew; Resnick, Andrew (Atlantic, 2025)
Grammy and Tony Award winning star Jonathan Groff leads the cast in the new musical that explore the life of singer Bobby Darin.